UNLEASHING ORGANIZATIONAL GROWTH THROUGH STRATEGIC TRAINING AND DEVELOPMENT: A QUALITATIVE INVESTIGATION - Ghatwal, Yashmita Yeshwant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Training and Development (T&D) interventions have been considered for a long time as a recipe for organizational success. Nevertheless, the strategic function of T&D in shaping organizational development has been qualitatively little explored. This research seeks to understand how T&D interventions designed strategically bring about organizational development through experience gained by employees working in industries. Through thematic analysis of semi-structured interviews and focus group discussions, four main mechanisms are revealed: skill development, leadership support, emotional commitment, and training effectiveness. Companies implementing emotional attachment, leadership involvement, and function-specific training in their T&D approach experience radical improvement in innovation, staff retention, and productivity. Theory and practice implications and directions for future research are laid out.